Clinical management of eosinophilic esophagitis – a nationwide survey among gastroenterologists in Germany - Miehlke, Stephan; von Arnim, Ulrike; Schlag, Christoph; Frieling, Thomas; Madisch, Ahmed; Loibl, Rudolf; Mainz, Dagmar; Labenz, Joachim (Zeitschrift für Gastroenterologie, 2019)
Background Eosinophilic esophagitis (EoE) is an increasingly recognized immune-mediated esophageal disease and a common cause for dysphagia and food bolus obstruction. The aim of this study was to evaluate the current clinical management of EoE among adult gastroenterologists in Germany.Methods We performed a cross-sectional study of 1393 adult gastroenterologists using a questionnaire containing 22 questions to general, diagnostic, and therapeutic aspects of EoE. The self-administered online survey was conducted between November 2017 and February 2018. Data capture and analysis was performed using SurveyMonkey.Results The overall responder rate was 29.6 %. More than half of the responders (54.9 %) felt to observe a significant increase of EoE patients. The EREFS score was mostly either unknown (44.3 %) or not routinely used (52.2 %). If EoE was suspected, most responders obtained multiple esophageal biopsies (n = 3 – 4: 35.7 %; n > 4: 61.6 %). The preferred primary treatment was proton pump inhibitors (PPI) in 37.2 % and topical steroids in 35.0 % of responders. PPI regimens were highly diverse, with only half of responders using high-dose PPI regimens. Allergy testing was often initiated (always 25.4 %, sometimes 48.9 %). The most common dietary therapy was 6-food elimination diet (52 %), followed by allergy test-directed diets (16 %) and 2-food elimination diet (16.5 %). The majority of responders indicated a need for long-term treatment (i. e., 23 % of responders in > 50 % their patients and 47.7 % of responders in 25 – 50 % of their patients).Conclusions Among gastroenterologists in Germany, substantial variation in the adherence to published EoE guidelines appears to exist. This indicates the need for intensified education and national guidelines in order to optimize and harmonize the clinical management of EoE patients.
Keywords: eosinophilic esophagitis; dysphagia; bolus obstruction; proton pump inhibitor; corticosteroids; elimination diet; endoscopic therapy